Villous Adenoma Arising in the Native Bladder Mucosa and the Upper Urinary Tract With Coexisting Neuroendocrine Carcinoma Following Augmentation Cystoplasty. (June 2019) - Nayak, Anupma; Depasquale, Brittany; Vergara, Norge; Guzzo, Thomas A.; Lal, Priti
Villous adenomas arising in the bladder following augmentation cystoplasty procedures are exceedingly rare. Even rarer is their occurrence in the native bladder mucosa and the upper urinary tract. In this article, we present a unique case of multifocal recurrent villous adenoma involving native bladder mucosa of an augmented bladder, bilateral ureters, and renal pelvis, with coexistent foci of adenocarcinoma and neuroendocrine carcinoma, in a patient with history of augmentation colocystoplasty. We additionally discuss the pathogenesis of development of carcinoma in the setting of augmentation cystoplasty.